Education Financing Management in Special Needs Schools - Mohammad Jon Tasrif; Yudi Nur Supriadi; Moch. Hafid; Kartiwan Setiawan; Afif Alfiyanto (Jurnal Pendidikan dan Konseling (JPDK), 2023)
This study aimed to determine how education financing in Extraordinary Schools is managed. The research method used is a literature review. Based on a literature review of journal articles published in national journals, both unaccredited and sinta accredited, it shows that the education for children with special needs is growing day by day, and significant changes from the government, schools, regular students, parents, and society in general. The government shows this through various policies related to the provision of education for children with special needs, primarily related to education financing, as well as acceptance by schools and communities that give children with special needs wider opportunities to obtain education like other normal children so that children with special needs can develop their talents, interests, potentials so that they do not depend on others (independence).